Review artikel: efektivitas penggunaan fototerapi terhadap rinitis alergi pada ibu hamil - Mally Ghinan Sholih; Munir Alinu Mulki; Annisa Frastica Septi; Muhammad Ja'far Ash Shidiq; Nariyyah Fitriana; Shalum Putriyani; Yuni Lili Indriyani; Yuniar Fathil Ilmi (Journal of Pharmaceutical and Sciences, 2023)
Rhinitis is an inflammation of the mucous membrane of the nose that affects millions of people worldwide. Although there has been much research and development related to the management of rhinitis, there are still challenges in achieving effective treatment and optimal symptom control. The purpose of writing this article is to achieve effective treatment and optimal control of rhinitis symptoms. The writing method used is literature review by collecting primary references from international journals published in the last 10 years (2013-2023). Referrals are selected through the pubMed database with relevant keywords.  The results and discussion of this study include information on allergic rhinitis, rhinitis of pregnancy, hormonal changes during pregnancy, and commonly used medications. In the treatment of gestational rhinitis, the use of phototherapy can be the right choice. Based on articles that have been reviewed, it shows that treatment with phototherapy is more effective in overcoming the symptoms of allergic rhinitis. Phototherapy has a good effect on immunosuppressants and immunomodulators that can suppress the body's immune activity and also relieve inflammation.